Dynamics of soil phosphorus under different management practices for groundnut cultivation in calcareous Vertisols - YADAV, R. S.; JAIN, N. K. ,; MEENA, H. N. ,; BHADURI, D.; BHALODIA, P. K.; BHADARKA, M.; DESAI, D. (Journal of Soil and Water Conservation, 2017)
Continuous P-deposition in the soils due to poor recovery of applied P-fertilizer is the major concern for environmental as well as P-nutrition of plants. Soils having three different management practices namely i) polythene drip (PD); cultivation of groundnut on raised beds using polythene mulch and drip irrigation, ii) resource conservation (RC); groundnut followed by wheat in zero tillage with green manuring and iii) conventional system (CS); cultivation on flat bed with conventional nutrient and water management practices were used and characterized for different P-fractions. The availability of soil phosphorus was highest under polythene drip (15 to 29 mg kg-1) followed by resource conservation (12 to 20 mg kg-1) and least under conventional systems (9-13 mg kg-1) depending on inputs used. The soil P was increased by 6 to 15% for inorganic and by 3 to 7% for organic fractions under these management practices (i.e., PD and RC) as compared to CS. The highest soil inorganic-P were recovered from PD>RC>CS in water soluble and mineralizable pools, CS>PD>RC in labile pool and RC>CS>PD in stable pool. Similarly the soil organic-P were recovered in the order of CS>RC>PD for soluble and labile pools and PD>RC>CS for mineralizable and stable pools. More than 50% of the soil phosphorus in these soils was recovered under bio-available pool which could be available for plant nutrition using appropriate management strategies. Overall the polythene drip and resource conservation management practices were found promising for creating congenial conditions to solubilize and mobilize the soil phosphorus in to different conceptual pools in the soil.